(untitled) (The Initiation, 2011)
Fiscal policy instruments such as royalty, tax, subsidy and market systems are core components of forest policy and have significant consequences on the management of the forest resources and their benefits to local communities. In this paper, we have examined the legal provisions of the fiscal instruments employed in Community Forestry of Nepal mainly based on the review of current policy documents. In addition, interviews and group discussions were also conducted with government units, traders and forest user groups in Parbat, Baglung and Dolakha districts. Inconsistencies and contradictions are seen mainly in handing over of community forest to local people, controlling taxation system, ban to export NTFPs and sharing revenues between government units and forest user groups. Consequently, such inconsistent provisions have affected the promotion of sustainable and market-oriented management of forest resources, coordination between local and central government authorities, and the overall financial situation of forest user groups. DOI: http://dx.doi.org/10.3126/init.v4i0.5539 The Initiation Vol.4 2011 82-91